A numerical study on the structural integrity of self-anchored cable-stayed suspension bridges (Fracture and Structural Integrity, 2016)
A generalized numerical model for predicting the structural integrity of self-anchored cable-stayed suspension bridges considering both geometric and material nonlinearities is proposed. The bridge is modeled by means of a 3D finite element approach based on a refined displacement-type finite element approximation, in which geometrical nonlinearities are assumed in all components of the structure. Moreover, nonlinearities produced by inelastic material and second order effects in the displacements are considered for girder and pylon elements, which combine gradual yielding theory with CRC tangent modulus concept. In addition, for the elements of the suspension system, i.e. stays, hangers and main cable, a finite plasticity theory is adopted to fully evaluate both geometric and material nonlinearities. In this framework, the influence of geometric and material nonlinearities on the collapse bridge behavior is investigated, by means of a comparative study, which identifies the effects produced on the ultimate bridge behavior of several sources of bridge nonlinearities involved in the bridge components. Results are developed with the purpose to evaluate numerically the influence of the material and geometric characteristics of self-anchored cable-stayed suspension bridges with respect also to conventional bridge based on cablestayed or suspension schemes.
Keywords: Self-anchored cable-stayed suspension bridges; Structural integrity; Nonlinear; Plasticity; Ultimate behavior; Finite element method